Marco Caracciolo, The Experientiality of Narrative. An Enactivist Approach (ENTHYMEMA, 2014)
Review of Caracciolo, Marco. The Experientiality of Narrative. An Enactivist Approach. Berlin: De Gruyter, 2014. Print.
Keywords: Enactivism; experientiality; interpretation; narrative